Land Deed Record, Wayne County, 1881 - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1881)
Land Deed Record, Wayne County, 1881. One handwritten record on official form. Deed from David J. Cooper to Emma A. Wakely, for 1200 acres. Wayne County, Georgia. August 8, 1881. 1 page.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Records and correspondence; Court records; Wayne County (Ga.)